Fracture characterisation of Karoo aquifers - Pacome, Ahokpossi Dehouegnon (University of the Free State, 2014)
Fractures are mechanical ruptures in rocks, form by stress (lithostatic, tectonic, and thermal stresses and high fluid pressures) concentrations around flaws, heterogeneities, and physical discontinuities at a variety of scales. In groundwater reservoirs, mainly in those formed within relatively less permeable or hard rocks, connected fractures may form privileged conduits for fluid flow and solute through the rock, and therefore needs to be located and quantitatively (geometry, permeability, and ability to transport solute) appreciated for a better understanding of water flow and mass transport processes in the subsurface. Many techniques have been adapted from petroleum applications to address these issues and are reviewed in the present study with after an overview on geological and geo-mechanical features that evolve fracturing. Very few existing tools are cost-effective and easy to be performed on the field. The FEC (Fluid Electrical Conductivity) based techniques; mainly the single borehole based ones involve often, relatively cost effective equipments and are simple. The present study focus also on the applicability of ―Flowing Fluid Electrical conductivity logging‖ (Tsang et al., 1990; Doughty et al., 2005) and the FEC based dilution test (well dilution) for fracture characterization in the Karoo aquifer. The FFEC is found to be a promising technique for local fracture characterization, mainly in contamination studies (investigation and scenario testing), like in mine environments; and is recommended to be experienced in South-Africa, particularly in the meta-sediments of the Karoo environment. The FEC based dilution test (well dilution) is gaining interest in fracture characterization in South Africa (Mohr Samuel and van Biljon Willem., 2009; Lasher Candice et al., 2009) and has been assessed on two experimental fields in the Karoo Aquifer. The technique is found to constitute a powerful tool for detection of flowing fractures and for qualitative interpretation. The Drost et al (1968) analytical solution suggested for the analysis of the test data (Cook et al., 2001a; Love et al., 2002) have been applied and yielded semi-quantitative values that can be used as first estimation of the groundwater velocity from flowing points into the studied boreholes. However, due to non ideal condition, refinements are still needed mainly for the field procedure and for the consideration of the mass circulation that may be associated with density gradient along the borehole.
Dissertation (M.Sc. (Institute for Groundwater Studies))--University of the Free State, 2010
Keywords: Aquifers -- Fracture -- South Africa -- Karoo; Groundwater -- South Africa -- Karoo; Electrical conductivity; Tracer concentration; Dilution